2001
DOI: 10.1508/cytologia.66.197
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and Molecular Evidence forWolbachia Infection in Uzi Flies of Exorista Species.

Abstract: The cytoplasmically inherited bacterial symbiont, Wolbachia is well known for inducing a variety of reproductive abnormalities in the diverse arthropod hosts it infects. Wolbachia has been implicated in causing cytoplasmic incompatibility, parthenogenesis, and the feminization of genetic males in different hosts. In the present investigation, electron microscopy and PCR technology was applied on uzi flies of Exorista species (Diptera: Tachinidae), serious pests of silkworm Bombyx mori L. TEM examination of uzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
6
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
(19 reference statements)
5
6
0
Order By: Relevance
“…These primers only amplified fragments from infected insects. Thus, the results we obtained in the present study using wsp primers demonstrate that Wolbachia was present in E. sorbillans (see also, Madhu and Puttaraju, 2001) and B. zebina. It is also evident from this study that Wolbachia was not present in any of the silkworm species or races.…”
supporting
confidence: 80%
“…These primers only amplified fragments from infected insects. Thus, the results we obtained in the present study using wsp primers demonstrate that Wolbachia was present in E. sorbillans (see also, Madhu and Puttaraju, 2001) and B. zebina. It is also evident from this study that Wolbachia was not present in any of the silkworm species or races.…”
supporting
confidence: 80%
“…The ultrastructure of Wolbachia found in the silkworm parasitoid uzifly, Exorista sorbillans, is extremely similar to that of Wolbachia pipientis (Madhu and Puttaraju, 2001) and to that of Wolbachia-like organisms described in other insects (Hsiao and Hsiao, 1985;Binnington and Hoffman, 1989). The present study found that the Wolbachiauzifly association represents a typical mutual symbiosis and Wolbachia has shown a beneficial effect on uzifly, Exorista sorbillans.…”
Section: Discussionsupporting
confidence: 79%
“…The presence of Wolbachia in this pest has been reported previously (Madhu and Puttaraju, 2001;Puttaraju and Madhu, 2002) from our laboratory by using molecular and cytological techniques, and it was found that, structurally, the Wolbachia present in the uzifly are similar to those of Drosophila and Culex. We present in this report further data resulting from crosses between infected and uninfected uzifly populations and intragenomic genetic conflict.…”
Section: Described This As Wolbachia Pipientissupporting
confidence: 77%
“…Though there are a number of curative measures, the loss of agro-products continues to be 25-30%. Our earlier work showed that some insects and pests of sericulture harbour Wolbachia (Madhu and Puttaraju 2001;Puttaraju and Madhu 2002;Prakash and Puttaraju 2006a) and suggested a novel method for the management of uzifl y, a parasitoid of silkworn (Puttaraju and Prakash 2005a;Puttaraju and Prakash 2005b;Puttaraju and Prakash 2005c;Prakash and Puttaraju 2006b). In the present paper we demonstrate the frequency of double versus single infection of Wolbachia using ftsZ A-and B-specifi c primers (Prakash 2006) in some insects and pests associated with mulberry and silkworn.…”
Section: Frequency Of Infection With a And B Supergroupmentioning
confidence: 99%